Induced sputum in asthma - Spanevello, Antonio (Henry Stewart Talks, 2013)
Induced Sputum: facilities and procedure, Induced Sputum as a biomarker of airway disease in asthma, Comparison with other techniques, Reference values and comparison between healthy and patients, Induced sputum in asthma: clinical implications